Attracting Prospective Professional Accountants Before and After the CPA Merger in Canada1. (June 2017) - Brouard, François; Bujaki, Merridee; Durocher, Sylvain
Abstract: As part of the unification of the Canadian accounting profession, a lot of effort has been devoted to organizational structures and systems. In these times of change, recruitment of prospective professional accountants remains an important factor for the Canadian and international development of the profession. In this paper, we explore professional accountants' recruitment by accounting associations in Ontario before (CA, CGA, CMA) and after (CPA) the merger of the three professional accounting associations. We use a legitimacy framework to make sense of the recruitment website content of each association. We find, in the post‐merger period, that the CPA profession adopts a more passive approach to legitimacy management, focusing mainly on exchange aspects of legitimacy, whereas prior to the merger a wider range of legitimacy management strategies were deployed by the predecessor associations. Important implications ensuing from our study are discussed.